Creating controversy: developing a virtual reality training tool with 360° film to engage in ethnic profiling reform - Böing, Bas; De Vries, Peter W.; Giebels, Ellen (Frontiers in Virtual Reality, 2025)
Ethnic profiling is a topic that is challenging to address in policing communities. Many police officers doubt its existence or find it too trivial and irrelevant to worry about. Others may find it important, but do not feel psychologically safe to discuss it with their colleagues. Many police officers, therefore, ignore training and conversations on ethnic profiling, which hinders combating it. We describe the foundations of a Virtual Reality based training prototype that seeks to encourage active participation in ethnic profiling dialogue. We describe the iterative process between the various steps in the design process of the Virtual Reality tool and the design features including experiential learning and perspective-taking on the individual level, and constructive controversy dialogue on the group level. Our observations during its testing phase indicate that the current prototype contributes to officers’ awareness of ineffective and biased police practices. While this testifies to the potential of the prototype design to shape meaningful police reform activities on a larger scale, we also speculate that our immersive design may offer solutions for other urgent socio-political controversies.